Effect of preeclampsia on human milk cytokine levels - Freitas, Natália Alves de; Santiago, Luiza Tavares Carneiro; Kurokawa, Cilmery Suemi; Meira Junior, José Donizeti de; Corrente, José Eduardo; Rugolo, Ligia Maria Suppo de Souza (Taylor & Francis, 2018)
Introduction: Preeclampsia (PE) is a systemic inflammatory disease, and its effect on human milk immune components is poorly understood. Objective: To investigate whether PE affects human milk cytokine levels. Methods: This was a prospective observational study involving mothers diagnosed with PE and with singleton pregnancy with no fetal malformation. The following cases were excluded: diabetes, chorioamnionitis, use of illicit drugs and alcohol, mastitis and congenital infection. In total, 228 mothers were studied and divided into two groups matched by gestational age: PE (n = 114) and normotensive (control, n = 114). Colostrum was collected from 24–72 hours postpartum, and mature milk was collected at the end of the first month. Cytokines (IL-1β, IL-6, IL-8, IL-10, IL-12, and TNF-α) were measured using flow cytometry. A generalized linear model with a gamma distribution was used to analyze the differences between groups versus time interaction. Results: The mean gestational age was 36 weeks. Increased IL-1 and IL-6 levels and reduced IL-12 levels in the colostrum were detected in PE, while in the mature milk, the IL-6 and IL-8 levels were lower than those of the control group. Conclusions: PE is associated with increased levels of inflammatory cytokines in colostrum and decreased levels in mature milk.
Keywords: colostrum; cytokines; human milk; inflammation; Preeclampsia